IMPLEMENTASI METODE PROJECT ORIENTED PROBLEM BASED LEARNING (POPBL) UNTUK MENINGKATKAN HASIL BELAJAR FIKIH SISWA DI KELAS VIII MTs AL-HIDAYAH AIR HITAM GEBANG - Fitri Popyta Sari; Abdul Halim; Zaifatur Ridha (LPPM STKIP AL MAKSUM, 2022)
The learning outcomes of class VIII MTs Al-Hidayah Air Hitam Gebang on Jurisprudence subjects, the material on Prostrate Sahwi, Prostration of Gratitude and Prostration of Recitation before applying the project-oriented problem-based learning model has not been completed. This can be seen from the average score of the students' pretest results. The process of implementing Fiqh learning in class VIII of MTs Al-Hidayah Air Hitam Gebang by applying the project oriented problem based learning method according to the plan that has been made, learning activities are carried out by no longer giving pretests to students, before starting learning the teacher motivates students to be more active than the previous meeting. The next step is still in the teacher's guidance in the form of class percentage actions and group work. The learning outcomes of class VIII MTs Al-Hidayah Air Hitam Gebang in the subject of project oriented problem based learnings material about Sujud Sahwi, Sujud Syukur and Sujud Tilawah, after the application of project oriented problem based learning methods have increased student learning outcomes.